Programación Neurolingüística en la mejora del aprendizaje de los estudiantes universitarios de la Universidad Andina Néstor Cáceres Velásquez - Fernández Villarroel, Roger Álvaro (2022)
Neurolinguistic Programming (NLP) provides tools for optimal communication, it provides instruments to change behaviors, skills, which limit or prevent the achievement of academic and personal goals. The objective of this research was to identify the characteristics of student learning and the communication styles of teachers towards students. The study is descriptive, developed in three stages: a) Documentary review. b) A questionnaire was elaborated with a Likert-type scale, validated by three experts and using Cronbach's alpha of 0.805. c) The results were systematized by means of simple statistical tables. It can be observed that the highest positive correlations were between the NLP meta-programs of attitude towards a situation and learning strategies. It is concluded that, there is a weak relationship between the variables and it can be observed that the positive correlations are between the NLP metaprograms of attitude to a situation and learning strategies. Therefore, there is a need to implement teacher induction courses to improve communication with students and achieve meaningful learning.